(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Road transport is considered the main axis of transportation in Syria and constitutes the largest percentage of the transport sector in Syria, due to the distinctive nature, environment and geographical location of Syria, therefore this type of transportation can play an important role in the process of economic growth if it is invested in an optimal and appropriate manner to the requirements of the Syrian economy. However, there has been a noticeable slow and weak progress in road transport investments. This study aimed to try to reach a model capable of determining the optimum level of investment in road transport in a way that serves the development of the Syrian economic and social economy requirements in the long term by studying the impact of quantitative road transport indicators on economic growth where the descriptive and analytical approach was used in a study and clarification The role of road transport indicators on sustainable development in the Syrian Arab Republic during the study period, and the standard method was used to study data on the Syrian Arab Republic between (1990-2018) and reach a set of conclusions.